The Great Change - Jack Wagner (Trinidad Press, 1979)
Detailed socialist eutopia using a version of the “sleeper wakes” in which a labor leader in the mid-twentieth century comes back to San Francisco in 2012. Quite a bit on the transition. Much is provided free or inexpensively. Much more on the details of the workplace and production than in many comparable works. Partnership between management and unions. Annual turnover in many leadership positions. A lot of bureaucracy but working the way it should.
Keywords: Male author; US author